Cerebellum: What is in a Name? Historical Origins and First Use of This Anatomical Term - Voogd, Jan (Cerebellum, 2020)
In this paper, we study who first used the Latin anatomical term “cerebellum” for the posterior part of the brain. The suggestion that this term was introduced by Leonardo da Vinci is unlikely. Just before the start of the da Vinci era in the fifteenth century, several authors referred to the cerebellum as “cerebri posteriorus.” Instead, in his translation of Galen’s anatomical text De utilitare particularum of 1307, Nicolo da Reggio used the Latinized Greek word “parencephalon.” More peculiar was the Latin nautical term “puppi,” referring to the stern of a ship, that was applied to the cerebellum by Constantine the African in his translation of the Arabic Liber regius in the eleventh century. The first to use the term “cerebellum” appears to be Magnus Hundt in his Anthropologia from 1501. Like many of the anatomists of this period, he was a humanist with an interest in classical literature. They may have encountered the term “cerebellum” in the writings by classical authors such as Celsus, where it was used as the diminutive of “cerebrum” for the small brains of small animals, and, subsequently, applied the term to the posterior part of the brain. In the subsequent decades of the sixteenth century, an increasing number of pre-Vesalian authors of anatomical texts started to use the name “cerebellum,” initially often combined with one or more of the earlier terms, but eventually more frequently in isolation. We found that a woodcut in Dryander’s Anatomia capitis humani of 1536 is the first realistic picture of the cerebellum.